2012
DOI: 10.1097/dcr.0b013e3182617716
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Postoperative Intra-abdominal Septic Complications after Bowel Resection in Patients with Crohn’s Disease

Abstract: Penetrating type, operation time >180 minutes, and handsewn anastomoses significantly increased the risk of postoperative intra-abdominal septic complications in Crohn's disease. Postoperative intra-abdominal septic complications had a negative influence on the short-term outcome in Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 16 publications
5
41
1
1
Order By: Relevance
“…These results are further complicated by a study including preoperative nutritional supplementation in patients with albumin less than 3.0 mg/dL (31). Moreover, albumin level less than 3.5 mg/dL (34,35) and less than 4.0 mg/dL (36) were reported to have no association with IASC. A recent meta-analysis using many of these described studies found a correlation with low albumin and increased risk of IASC (37), but the definition of low albumin is quite inconsistent in these studies making even the pooled results difficult to determine.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…These results are further complicated by a study including preoperative nutritional supplementation in patients with albumin less than 3.0 mg/dL (31). Moreover, albumin level less than 3.5 mg/dL (34,35) and less than 4.0 mg/dL (36) were reported to have no association with IASC. A recent meta-analysis using many of these described studies found a correlation with low albumin and increased risk of IASC (37), but the definition of low albumin is quite inconsistent in these studies making even the pooled results difficult to determine.…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, abscess was not associated with abdominal complications in other studies (35,36). Some studies included abscesses that were drained preoperatively and found no association with abscess and postoperative IASC (36,41). A meta-analysis which included a large number of studies that discussed intra-abdominal abscess found an increased risk of IASC with intra-abdominal abscess.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This high rate of morbidity is in relationship with long-term medical treatment: corticosteroid-therapy and immunosuppressive drugs. Risk factors for septic complications occurred post-operatively are: presence of abscess discovered during surgery, the severity of disease, perioperative malnutrition, long-term corticosteroidtherapy, Penetrating type, operation time >180 minutes, and handsewn anastomoses [27,50,51].…”
Section: The Early Postoperative Resultsmentioning
confidence: 99%
“…Side to side stapled anastomosis is as safe as conventional sutured end-to-end anastomosis and results in a lower incidence of symptomatic recurrent Crohn's disease and need for reoperation. [27,28]. For colonic lesions: segmental colonic, sub-total or total colonic resection.…”
Section: The Intestinal Resectionmentioning
confidence: 99%